Three worlds in Farida Afro’z’s triplets: lines of classical, present and future poetry - Atabayeva Guljahon Zufarovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Every aspect of the verse changes, renews and develops over time in garmony with society. Literature is no exception. On the basis of the classical literary genre “musallas”, with new formal and spiritual developments, the the genre of “triplets”, including “rosary”, arose. Genesis of three-line genres in Article, poetics of rosaries by Farida Afroz.